Effects of Fibulin-5 Gene Silencing on Proliferation and Apoptosis of IgG4-ROD Lacrimal Gland Fibroblasts - Huarong Wu; Daikun Lei; Xiaoling Zhang; Mengfei Wang; Yuanyuan Wang; Jie Xia; Fan Chen; Bei Chen; Yanming Tian (Stem Cells International)
Objective. This study is aimed at discussing the value of RNA interference technology on inhibiting lacrimal gland fibrosis in IgG4-related ocular disease (IgG4-ROD). Methods. Six patients with IgG4-ROD who came to the hospital for surgical treatment from October 2018 to August 2019 were selected, and their diseased lacrimal glands were taken for primary cell culture and fibroblast identification. High efficiency and specificity small interference RNA (siRNA) plasmid vector was constructed, its inhibitory effect on fibroblast proliferation was determined by CCK-8 assay, and the appropriate concentration was selected as the siRNA concentration for subsequent experiments. RT-PCR and Western blot detected the relative expression levels of Fibulin-5 mRNA and protein in the cells 48 hours after transfection. The apoptosis rate of each group of cells at 24 hours, 48 hours, and 72 hours after transfection was detected by flow cytometry, and the proliferation and apoptosis of cells after silencing Fibulin-5 were analyzed and compared. Results. 24 hours after transfection, there was no significant difference in the proliferation rate among the four groups (P>0.05); 48 hours and 72 hours after Fibulin-5 siRNA transfection, the proliferation activity of the transfected cells was significantly decreased compared with the 0 nM group, and the inhibitory effect of 75 nM siRNA was the strongest. The expression of Fibulin-5 mRNA and protein in the siRNA-transfected cells was significantly decreased compared with the blank and empty vector negative siRNA groups, and the difference was statistically significant (P<0.05). The apoptosis rate of cells in the Fibulin-5 siRNA transfection group was significantly higher than that of cells in the blank and empty vector negative siRNA groups, and the difference was statistically significant (P<0.05). Conclusion. Fibulin-5 siRNA recombinant plasmid can significantly downregulate the mRNA and protein expressions of target gene Fibulin-5 and promote apoptosis after transfection into IgG4-ROD lacrimal gland fibroblasts. It is speculated that Fibulin-5 can be used as a target to effectively inhibit the fibrosis of lacrimal gland tissues by RNAi technique.